Gonorrhoea – current threat? Epidemiological analysis of gonococcal infections - Ruszel, Kinga; Pokorski, Piotr; Szczęsna, Halina Piecewicz (Journal of Education, Health and Sport, 2019)
Sexually Transmitted Diseases (STD’s) are diseases transmitted via sexual contacts by reproductive system as well as urinary system. Many patients have encountered easily treatable STDs which pose no relative threat to the patient’s health, however increasing numbers of people struggle against infections resistant to treatment, which may lead to death. Both immunocompetent patients and those with a compromised immune system may develop bacterial infections. STDs include diseases such as bacterial vaginosis, cytomegalia, candidiasis, trichomoniasis, syphilis, chlamydia and gonorrhoea. The aim of the following article is to present the most important information on Neisseria gonorrhoeae and data regarding gonorrhoea morbidity over the 2008-2018 period. The article discusses the epidemiology, symptomatology, diagnostic procedures and treatment of gonorrhoea infections in closer detail. Data used in the article comes from research studies, most recent recommendations, guidelines and bulletins from the National Public Health Institute (PZH).